2018
DOI: 10.1051/0004-6361/201833019
|View full text |Cite
|
Sign up to set email alerts
|

Centaurs potentially in retrograde co-orbit resonance with Saturn

Abstract: Aims. 2015 BZ509 is the first asteroid confirmed to be in retrograde co-orbit resonance (or 1/-1 resonance) with the giant planets in the solar system. While Saturn is the only giant planet whose Trojans are not discovered until now, we identify some small bodies among Centaurs and Damocloids that are potentially in 1/-1 resonance with Saturn in the present study. Methods. We integrate numerically the motion of the 1000 clones (include the nominal orbit) of each Centaur whose orbit has a semimajor axis between… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…In our recently published paper, Li et al (2018) identifies four candidates potentially trapped in the retrograde 1:1 resonance with Saturn, 2006RJ2, 2006BZ8, 2017SV13, and 2012 YE8. Among these candidates, only 2006 RJ2 has a relatively long-time resonant state with Saturn (above 100 kyr), in which the resonant Kozai-Lidov dynamics is able to influence the orbital evolution of the minor body significantly.…”
Section: Rj2mentioning
confidence: 99%
See 1 more Smart Citation
“…In our recently published paper, Li et al (2018) identifies four candidates potentially trapped in the retrograde 1:1 resonance with Saturn, 2006RJ2, 2006BZ8, 2017SV13, and 2012 YE8. Among these candidates, only 2006 RJ2 has a relatively long-time resonant state with Saturn (above 100 kyr), in which the resonant Kozai-Lidov dynamics is able to influence the orbital evolution of the minor body significantly.…”
Section: Rj2mentioning
confidence: 99%
“…Moreover, we compare the numerical results in a CRTBP model with the semianalytical phase-space portraits. In Section 4, we utilize this method to analyze the Kozai-Lidov state of two real minor bodies inside the retrograde 1:1 resonance, they are, 2015 BZ509 and 2006 RJ2, the latter is confirmed to be in the retrograde 1:1 resonance with Saturn by Li et al (2018). Finally, in Section 5, we apply this methodology to two more retrograde resonances, 2:1 and 2:5, and find different bifurcations of equilibrium points with phase-space portraits.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Connors & Wiegert (2018) reported that asteroid 2007 VW266 (a retrograde object near Jupiter's orbit) is inside a retrograde 13:14 resonance with Jupiter. Li et al (2018) numerically explored the resonant behaviors of the clones for the minor bodies among Centaurs and Damocloids and they identified another four Centaurs (including 2006RJ2, 2006BZ8, 2017SV13 and 2012, which are potential candidates inside retrograde co-orbital resonances with Saturn. Furthermore, Li et al (2019) numerically investigated the possible retrograde resonant configurations of minor objects in the Solar system and they identified 38 asteroids to be trapped inside retrograde MMRs with planets.…”
Section: Introductionmentioning
confidence: 99%
“…It seems that former researchers have put an end to the problem. However, the latest discoveries of the first retrograde co-orbital body of Jupiter (Wiegert et al 2017) and potential retrograde co-orbitals of Saturn (Li et al 2018) have once again ignited our curiosity to the co-orbital region of Saturn. In the process of studying the dynamics of retrograde resonances (Huang et al 2018a,b), we noticed that Saturn's retrograde co-orbital region is significantly unstable.…”
Section: Introductionmentioning
confidence: 99%